A cornual ectopic pregnancy case: diagnosis, etiology and its management (Medical Journal of Indonesia, 2009)
This is a report of a case of cornual ectopic pregnancy, with transvaginal ultrasonography done for early detection, screening, β-hCG measuring, also discussed was the role of methotrexate therapy prior to operative procedure with conservative management. Multiple intramural myomas (22 myomas) in this case were strongly believed as the etiology of the cornual pregnancy. (Med J Indones 2008; 18: 64-8) Keywords: Cornual ectopic pregnancy, multiple myomas, ultrasonography, methotrexate